CLINICAL FEATURES AND OUTCOME OF STAPHYLOCOCCUS AUREUS BACTEREMIA FROM A TERTIARY CARE HOSPITAL IN PAKISTAN - Javaid, Shehnila; Nasim, Asma; Dodani, Sunil Kumar; Babar , Zaheer Uddin (Infectious Diseases Journal of Pakistan, 2022)
Background: Staphylococcus aureus bacteremia is known to be an independent risk factor for mortality and metastatic complications. It also carries high morbidity and mortality. There is limited clinical data on SAB from Pakistan. This study aimed to describe the clinical presentation and outcome of SAB from a tertiary care hospital. Material and Methods: A prospective cohort study done at Sindh Institute of Urology and Transplantation (SIUT) Karachi. All patients aged > 18 years with documented SAB were included. Demographics, clinical features and treatment were noted. Patients were followed at day 3 and 14 for complications and outcome. Outcome was recorded as microbiological cure and mortality. Results: Out of 92, 81(88%) were Methicillin resistant S. aureus (MRSA) and 11(12%) Methicillin sensitive S. aureus (MSSA). Overall, being on hemodialysis 72 (78%) and central line 68(73.9%) were the major risk factors of S. aureus bacteremia. In 66 (71.7%) patients, the source of SAB was dialysis lines. Significantly more patients with MSSA did not have source identified (p=0.009). Fever 75(81.5%) and hypotension 19 (20.7%) were the presenting symptoms. Significantly more patients with MSSA presented with severe disease such as altered level of consciousness, cardiac arrest and mechanical ventilation. Around, 22(24%) developed complications, MRSA had more complications than MSSA however, endophthalmitis (27%) was noted only in MSSA. Overall, 17(18%) died. Non survivors were more associated with acute renal failure, being on hemodialysis and no identifiable source, however not statistically significant. Conclusion: S. aureus bacteremia carries high mortality and major source was dialysis catheters in our cohort. Around one fourth of patients developed complications. MSSA bacteremia presented with significantly more severe disease while MRSA with complication however not statistically significant. Non survivors were more associated with hemodialysis, acute renal failure, unidentifiable source and complications. High staff to patient ratio with strict infection control measures needed to prevent SAB in dialysis patients.